TANGGUNG JAWAB KONSTITUSIONAL PEMERINTAH DALAM MENJAMIN HAK KONSTITUSIONAL ATAS INFORMASI DI ERA DIGITAL - Bahram, Muhammad (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this article is to examine how the government has a constitutional responsibility to protect citizens' right to information in the digital age. This research is driven by the increasing complexity of information access and dissemination, which is often not matched by adequate constitutional protection. This research was conducted using a normative method by performing a legal-critical analysis of the Indonesian constitution, laws and regulations, and digital policy practices. The main finding indicates that in the digital age, a passive government approach to protecting the right to information is no longer relevant. The government must change to act as a guarantor of rights, not just as a regulator. This article suggests human rights-based digital policy changes, as well as the establishment of an independent oversight body to ensure that the management of public information is transparent and accountable. The main conclusion emphasizes that inclusive digital constitutionalism is crucial as the foundation of the state to ensure citizens' digital rights fairly and genuinely.